ENHANCING CUSTOMER ACQUISITION THROUGH CREATIVE COMMUNICATION IN PERSONAL SELLING: A CASE STUDY OF PT TIRTA ASASTA DEPOK (PERSERODA) - Marpaung, Chintia Prasasty Natasha; Putra, Afdal Makuraga; Pandjaitan, Rosmawaty Hilderiah (Universitas prof. Dr. Moestopo (Beragama), 2024)
This research aims to explore the role of communication creativity in personal selling strategies to increase the number of customers in the Marketing Team of the Regional Water Company Tirta Asasta Depok in 2024. The method is an exploratory case study. Primary data was collected through interviews and direct observations, while secondary data was gathered from literature, company documents, and previous research. The theoretical framework includes Computer-Mediated Communication, Social Exchange Theory, and Media Convergence Theory. The research findings show that communication creativity in personal selling involves utilizing media convergence tools such as laptops, WhatsApp, email, and Zoom to interact and negotiate with customers. This strategy is further enhanced by offering rewards, providing gifts, and using motivational narratives to build relationships. It also includes delivering more comfortable services with improved negotiation management and collaborating with local authorities to expand outreach. As communicators, neat and polite appearances, along with the use of